Prarancangan Pabrik Dioktil Ftalat Dari Ftalik Anhidrat dan 2-Etil Heksanol Dengan Kapasitas 40.000 Ton/Tahun - Wijaya, Hamdan; , Nur Hidayati, Ph.D; , Dr. Ahmad Muhammad Fuadi (2016)
Industry as part of progress indicator of a country becomes a stimulus to fulfill modern people needs which happen to be complex from domestic range to industry level, as well as plasticized entity. Diocthyl phthalate is a plasticizer, a material support in the plastic industry that its consumption is happen to increase from year to year based on central Indonesia statistic data. Diocthyl phthalate industrial unit planned to be built at Gresik, East Java by 40.000 ton per year capacity. The industrial unit managed to produce diocthyl phthalate weigh 99,9% concentration using material base anhydrate phthalic 2.299,2859 kilograms per hour, 2-ethyl hexanol 11.922,8023 kilograms per hour, and sulfur acid catalyst 12,9414 kilograms per hour. Diocthyl phthalate production performed by etherification obtained in liquid stage with 150oC operation phase and 1 ATM, irreversible and exothermic non-adiabatic. The reactor utility is CSTR type or flow stirred tank reactor (RATB) with H2SO4 (Sulfur Acid) catalyst. The process support unit (utility) consists of water supplier and steam, with the need of water 2.458.853,59 kilograms per hour and steam 4953,9364 kilograms per hour. Electricity needs supplied by Nuclear Electricity Generator (PLN) 819,0353 kilowatt per hour, and the diocthyl phthalate industrial unit intended to be built by 16910 m2 wide territory and run by 158 employee. The settled financial capital needed to build this diocthyl phthalate industrial unit is IDR 1.190.988.467.490,00 and work funds by IDR 212.236.742.528,00. Economy analysis shows the annual profit before tax is IDR 188.971.940.414 and IDR 141.728.955.311 after tax (by 25%) per year. The percentage of Return On Investment (ROI) before tax 15,9% and after tax 11,90%. Whether the Pay Out Time (POT) before tax 3,87 year and after tax 4.57 year. Break Event Point (BEP) by 54,94% and Shut Down Point (SDP) by 23,70%. Summarized by these analysis is that this industrial unit is profitable and worth established.